2010
DOI: 10.1111/j.1439-0442.1974.tb01358.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of the Phosphatase Activity in the Semen of Bovines (Bos bubalis and Bos taurus) in Egypt

Abstract: Summary The paper records the average values of acid and alkaline phosphatases in 102 (first, second and third) ejaculates from buffalo, Friesian, and native bulls maintained at 3 different localities. The levels of these enzymes were studied in both whole semen and seminal plasma. The results were examined to reveal the difference between buffalo and cattle, and between consecutive ejaculates, and also the variation in phosphomonoesterase activity of semen in relation to the locality. Zusammenfassung Vergleic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
4
0

Year Published

2010
2010
2013
2013

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 11 publications
1
4
0
Order By: Relevance
“…In agreement with ABDOU et al (1974), buffalo semen was found to display almost 250 O / o and 200 O / o higher acid and alkaline phosphatases, respectively, than Friesian bulls. Although the phosphatases activities, like many other biochemical attributes of semen, may be governed by hereditary factors controlling the functional status of the reproductive organs in which they are synthesized, it seems likely that the semen content of these enzymes may vary greatly depending on the environmetnal conditions available at the time of ejaculation.…”
Section: Discussionsupporting
confidence: 62%
See 2 more Smart Citations
“…In agreement with ABDOU et al (1974), buffalo semen was found to display almost 250 O / o and 200 O / o higher acid and alkaline phosphatases, respectively, than Friesian bulls. Although the phosphatases activities, like many other biochemical attributes of semen, may be governed by hereditary factors controlling the functional status of the reproductive organs in which they are synthesized, it seems likely that the semen content of these enzymes may vary greatly depending on the environmetnal conditions available at the time of ejaculation.…”
Section: Discussionsupporting
confidence: 62%
“…
Detailed reviews (MANN, 1949;1964) on semen metabolism have emphasized the important role of dephosphorylating enzymes, particularly that of the phosphomonoesterases-acid and alkaline phosphatases, in sperm glycolytic reactions. The levels of seminal phosphatases as well as the relative proportions of the acid and alkaline enzymes are known to vary greatly from one species to another (BELL andLAKE, 1962, andMURDOCH andWHITE, 1968).Whenever comparisons between buffaloes and bulls were set up, it was obvious that the semen of buffaloes displayed significantly much higher activity of both enzymes (ROY et al, 1960;ABDULLA et al, 1973, andABDOU et al, 1974). The high content of phosphatases in buffalo semen together with the high concentration of phosphate esters was thought to favour the accumulation of inorganic phosphorus ions at a level which is likely to inhibit the respiration and viability of spermatozoa (ROY et al, 1960).
…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Phosphatases are found in seminal plasma, acrosomes, sub-acrosomal space, post nuclear cap, cytoplasmic droplets and tail specially the mid piece of spermatozoa (Guraya, 1987). Seminal plasma phosphatases are derived from the secretions of accessory sex glands (Abdou et al, 1974) and are involved in transport of calcium ions from external fluids of female genital tract (Restall and Wales, 1968).…”
Section: Introductionmentioning
confidence: 99%
“…
Reports on the enzymic composition of buffalo semen are few. Studies on the levels of some enzymes, particularly acid and alkaline phosphatases (ROY et al, 1960;ABDULLA et al, 1973 andABDOU et al, 1974), transaminases, lactic dehydrogenase and aldolase (CHAUHAN and SRIVASTAVA, 1973) revealed a picture quite different from that for bull semen. The difference in the activities of these and probably other enzymes may be responsible for the different biological behaviour and preservability of the semen of the two species.
…”
mentioning
confidence: 99%